Partial HELLP syndrome: case report - Dagar, Sheetal; Gupta, Monika; Shekhawat, Vrinda; Minhas, Santosh (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
HELLP syndrome is a complication in pregnancy clustered by haemolysis, elevated liver enzymes, and a low platelet count. It is seen as a serious complication of preeclampsia and eclampsia. Serious manifestations like haemorrhage, infarction, rupture and other hepatic manifestations are usually associated with it. In this case study, 29 years old primigravida is a booked case admitted in ward at 39 weeks 1 day with decreased fetal movement for 2 days. No history of pain abdomen, bleeding per vaginum, discharge per vaginum. Her blood pressure records at the time of admission was 110/72 mmHg and she was normotensive throughout pregnancy. Urine routine examination was negative for urinary protein. However, blood tests showed platelet count of 66,1000/cumm, with ALT of 174 U/L and AST of 123 U/L on peripheral blood film. RBC were predominantly normocytic, normochromic with few macrocytes. WBC has normal morphology. Platelets were reduced on smear. Giant platelets were seen. Ursodeoxycholic acid 300 mg 12 hourly were given to the patient and 3 doses of vitamin K I/M 24 hourly. She was delivered by cesarean section which was performed due to failure of progression of labor with a deflexed head. There was presence of retroplacental clot of 4×3 cm indicating placental abruption, a complication of HELLP syndrome. From this we conclude that we should be careful in suspecting complications of full blown diseases even when the patients are asymptomatic but have atypical laboratory findings.